2022
DOI: 10.1155/2022/4061713
|View full text |Cite
|
Sign up to set email alerts
|

Wumei Pill Ameliorates AOM/DSS-Induced Colitis-Associated Colon Cancer through Inhibition of Inflammation and Oxidative Stress by Regulating S-Adenosylhomocysteine Hydrolase- (AHCY-) Mediated Hedgehog Signaling in Mice

Abstract: Wumei Pill (WMP) is a traditional Chinese herbal formulation and widely used to treat digestive system diseases in clinical. S-Adenosylhomocysteine hydrolase (AHCY) can catalyze the hydrolysis of S-adenosylhomocysteine to adenosine and homocysteine in living organisms, and its abnormal expression is linked to the pathogenesis of many diseases including colorectal cancer (CRC). A previous study reported that WMP could prevent CRC in mice; however, the underlying mechanisms especially the roles of AHCY in WMP-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…Here, we determined RRP15 expression in an AOM/DSS-induced mice CAC model. Consistent with the previous studies [ 12 , 13 ], including ours [ 14 ], obvious tumorigenesis and shorter colon length were observed in the AOM/DSS-treated group than in the untreated group ( Figure 2 A). Interestingly, a significant increase in RRP15 expression was observed in the AOM/DSS-treated group than in the untreated group ( Figure 2 B).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we determined RRP15 expression in an AOM/DSS-induced mice CAC model. Consistent with the previous studies [ 12 , 13 ], including ours [ 14 ], obvious tumorigenesis and shorter colon length were observed in the AOM/DSS-treated group than in the untreated group ( Figure 2 A). Interestingly, a significant increase in RRP15 expression was observed in the AOM/DSS-treated group than in the untreated group ( Figure 2 B).…”
Section: Resultssupporting
confidence: 92%
“…To establish the AOM/DSS-induced mice CAC model, the detailed protocol can be referred to in our previous report [ 14 ]. The experimental procedures were permitted by the Institutional Animal Ethical Committee of Nantong University on 7 September 2020 (project identification code: S20200907-306) and performed by abiding to the NIH Guidelines for Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…Further results showed that inhibiting miR-222-3p reduced the levels of ROS and MDA in IECs, increased the level of GSH-Px, and reduced the levels of the inflammatory factors IL-1b and TNF-a in the supernatants of IECs (Figures 8L-P). Previous studies also showed that in the context of oxidative damage in CAC mice, the activities of the antioxidant enzymes GSH-Px and SOD in colon tissue were significantly reduced, and ROS and MDA levels were significantly increased (9,62). However, increasing the expression of Nrf2 and HO-1 can increase the activity of the antioxidant enzyme SOD, reduce the levels of MDA, inhibit the levels of the inflammatory markers NF-kB, TNF-a, IL-1b and MPO in CAC mice, and have a certain preventive effect on the occurrence of CAC (63,64).…”
Section: Discussionmentioning
confidence: 96%
“…WMP is widely used in clinical practice, and numerous researchers have explored its mechanisms. [14,[20][21][22][23] However, there is currently a gap in research concerning the common mechanisms of action of WMP in treating both UC and T2DM.…”
Section: Discussionmentioning
confidence: 99%